MEMBUDAYAKAN PERILAKU HIJAU DI KALANGAN PEKERJA: DARI SUDUT THE GREEN FIVE TAXONOMY - Abdull Razab, Muhamad Firdaus; Udin, Zulkifli Mohamed (Fakultas Ekonomi, UIN Maliki Malang, 2014)
Green practices in the organization’s environment is seen as one way of educating the workers tocontinue this practices into their living environment. Environmental issues has become a buzzword in thepresent because the incident that occurred and give impact such as global warming, landslides, air pollutionas well as pollution of the river which is now happen throughout the world. Based on a content-based modelfor green behaviour among workers to ensure environmental behavior to keep the sustainability. This taxonomyconsists of five parts, namely: avoiding harm, conserving, working sustainability, influencing others andtaking initiative.